Pengaruh Fundamental dan Makroekonomi terhadap Harga Saham pada Perusahaan Sektor Properti dan Real Estate - Hellena Putri Pramestika; Mujiyono (LPPM UNISDA, 2026)
The capital market serves as a source of funding for companies and an investment vehicle for the public, with corporate performance acting as the primary driver of investor appeal. Corporate performance is heavily influenced by macroeconomic conditions and the company's fundamental factors. This study aims to re-examine the impact of fundamental and macroeconomic factors on stock prices. Data from 105 property and real estate companies listed on the Indonesia Stock Exchange (IDX) between 2022 and 2024 were analyzed using multiple regression at a significance level of 0.05. The results indicate that ROA, firm size, and inflation have a significant partial effect on stock prices, whereas DER and GDP do not.